Development of Indonesian Halal Logistic: A Swot Approach - Rizki, Darlin; Jadidah, Wanti Nur; Al Afif, Rafiq Azzam; Akhtiar, Muhammad Najid; Athief, Fauzul Hanif Noor (Journal of Digital Marketing and Halal Industry, 2024)
Increasingly, consumers are becoming more aware of and concerned about the products they buy and consume. However, products labeled as halal do not necessarily guarantee high halal quality, as there is a potential for contamination due to insufficient monitoring of the distribution chain by the relevant halal authorities in Indonesia. This study aims to analyze the strengths and weaknesses of halal logistics, identify growth opportunities, and assess the threats faced, as well as determine the necessary actions for future development. Using a literature review approach, data were collected from search engine databases including Scopus, Google Scholar, Emerald, ScienceDirect, Taylor Francis, and Wiley Online Library, and then categorized into four SWOT categories. The findings indicate that the strengths of halal logistics lie in the large population and broad market segments, while weaknesses include regulatory issues and the lack of specialized halal logistics infrastructure. Opportunities could enable Indonesia to become a leading producer in the global halal trade, despite challenges such as the rise of counterfeit products and the production burdens associated with halal schemes. The final section of the study proposes relevant development strategies for stakeholders in the field of halal logistics. This research provides a reference for policy formulation and assessing the readiness of business actors and public consumption preferences regarding the halal concept. The findings underscore the need for comprehensive halal logistics regulations to ensure standardization, compliance, and security, while leveraging Indonesia's demographic strengths to promote halal products in international markets. The novelty of this research lies in identifying Indonesia's specific strengths and weaknesses in halal logistics and proposing strategies to enhance Indonesia's position as a global leader in branded halal trade.